Sosyal Bilgiler Öğretmenlerinin Sınıf Yönetimi Yeterliliklerine İlişkin Okul Yöneticilerinin Görüşlerinin Değerlendirilmesi - Sari, İsmail (Muş Alparslan Üniversitesi, 2018)
The purpose of this study is to examine theclassroom management competences of social studies teachers according to theopinions of school principals. The research is a descriptive study in thegeneral survey model. The data related to the research were gathered from theschool principals who work in state secondary schools in the Ergani District ofDiyarbakır during the spring semester of 2012-2013 academic year. The data weregathered by the "Classroom Management Assessment Scale". As a resultof the research, the classroom management proficiency levels of social studiesteachers were observed by the school principals at the level of"sufficient". According to the opinions of the school principals, itwas determined that the level of proficiency of social studies teachersregarding "activity management" was low. Additionally it was observedthat the opinions of the school principals related to the classroom managementcompetences of the social studies teachers did not show any significant differenceaccording to the age and seniority variables. Therefore, it is recommended thatsocial studies teachers should carry out studies that will enable them toimprove themselves in the dimension of activity management of classroommanagement.

Buaraştırmanın amacı, sosyal bilgiler öğretmenlerinin sınıf yönetimiyeterliliklerini okul yöneticilerinin görüşleri doğrultusunda incelemektir.Araştırma, genel tarama modelinde betimsel bir çalışmadır. Araştırmaya ilişkinveriler, 2012-2013 eğitim-öğretim yılı bahar döneminde Diyarbakır’ın Erganiİlçesindeki devlet ortaokullarında görev yapan okul yöneticileri üzerinden eldeedilmiştir. Veriler, "Sınıf Yönetimi Becerisini Değerlendirme Ölçeği"aracılığıyla toplanmıştır. Araştırma sonucunda, sosyal bilgiler öğretmenlerininsınıf yönetimi yeterlilik düzeyleri okul yöneticileri tarafından “yeterli”seviyesinde gözlemlenmiştir. Okul yöneticilerinin görüşlerine göre, sosyalbilgiler öğretmenlerinin “etkinlik yönetimine” ilişkin yeterlilik düzeylerinindüşük düzeyde olduğu saptanmıştır. Ayrıca, yaş ve kıdem değişkenlerine göre, sosyal bilgiler öğretmenlerinin sınıf yönetimi yeterliliklerine ilişkin okulyöneticilerinin görüşlerinin anlamlı bir farklılık göstermediğigözlemlenmiştir. Dolayısıyla, sosyal bilgiler öğretmenlerinin sınıf yönetiminin“etkinlik yönetimi” boyutunda, kendilerini geliştirmelerine olanak sağlayacakçalışmalar yapılması önerilmektedir.
Evaluating the Views of the School Principals, Concerning the Proficiency Level of Social Studies Teachers in Classroom Management
anemon
Keywords: Social Studies Teacher; Classroom Management; Proficiency; Sosyal Bilgiler Öğretmeni; Sınıf Yönetimi; Yeterlilik